Economic polarisation in Europe - Kapeller, Jakob,Gräbner-Radkowitsch, Claudius,Heimberger, Philipp (ifso, Institute for Socio-Economics, University of Duisburg-Essen, 2019)
This study discusses the challenges that economic policy-makers in Europe have to cope with, in order to ensure an economically prosperous and institutionally stable community of Member States of the European Union (EU). At the analytical level, we not only document a process of multi-dimensional polarisation of EU countries, but also link the existing economic divergences with a central long-term problem, namely structural polarisation: differences in the institutional and legal embedding (e.g. in the areas of tax and corporate law, the labour market or the financial sector) and in technological capabilities are a major driver of divergence in living standards between some Member States. This polarisation, which started even before the financial crisis but has intensified over the last ten years, is due largely to the global and the European
10419/215637
Keywords: Graue Literatur; Europe; European integration; economic openness; competitiveness